LANDSLIDE PECULIARITIES PHENOMENA ON THE TERRITORY OF THE REPUBLIC OF ARMENIA (Proceedings of the YSU C: Geological and Geographical Sciences, 2016)
The work is dedicated to landslides, occurring in Armenia and the main types of landslide deformations. For each of the five areas identified by geotectonic features, the engineering geological conditions, including landslides and mechanisms of their occurrence is presented. The following landslide deformations are singled out for landslides occurring in Armenia: landslides, flows, slidings, avalanches, plastic landslides and complex transition landslides.
Keywords: landslides mechanisms; geotectonic deformations; geological engineering; sliding; avalanche